Perception of transformational leadership style and its effectiveness on virtual work-teams (VWT). A literature review in the organizational context - Varela Medina, Néstor Daniel (2018)
This article presents the development of different studies in perception of the transformational leadership style applied in virtual work-teams (VWT). The approached phenomenon’s study method was conducted through a literature review in transformational leadership and VWT’s, to comprehend and stablish their importance in organizations. Results could provide VWT leaders with pertinent information to counteract distance and time difficulties. Findings determined leadership capability generates effectiveness in changing global business scenarios, as an adequate response of VWT’s at the organizational arena.